EFFECTS OF CANOPY CONDITION AND RAMET CLASS ON CLONAL PLASTICITY OF DWARF BAMBOO, FARGESIA DECURVATA, IN AN EVERGREEN BROADLEAVED FOREST IN THE JINFO MOUNTAINS, CHINA - Chang-Gen Lin#; Ai-Ming Cai#; Zhen Li; Rong Yan; Lie Xu; Ping Zhang; Yong-Jian Wang (Journal of Animal and Plant Sciences, 2017)
Dwarf bamboo, a dominant understory clonal plant in temperate forests, is recognized to be an key factor for forest regeneration. However, none has examined effects of canopy condition and ramet class of connected clonal system. In a field experiment, clonal plasticity in a four-connected ramet system of dwarf bamboo, Fargesia decurvata were studied under canopy, small gap, medium gap and large gaps in an evergreen broadleaved forest in the Jinfo Mountains, China. In the ramet system level, morphology traits of F. decurvata were significantly highest in the medium gap, and smallest in the canopy. Traits of rhizome, spacer and biomass were significantly higher in the large and medium gap than in the small gap and canopy. Canopy condition had a similarly significant effect on traits of morphology, clonal growth and biomass of each ramet component of F. decurvata. Number of leaves, total leaf area and shoot biomass were lower, but number of ramets was significantly higher in distal ramet (D class) than those in other three classes. Number and node length of spacers and total spacer length significantly increased in C-D class from forest canopy to large gap, but there was no significant effects in other classes, as a interactive effects of canopy condition and ramet class on spacer traits. Thus, these results indicated a positive influence of gap size on spacer traits of distal ramets of F. decurvata. Therefore, interaction of canopy condition and internal age class of ramet system might lead to population adaptation to environmental differences, which shapes plasticity in traits of morphology, clonal growth and biomass of dwarf bamboo in different forest conditions.
Keywords: Fargesia decurvata; spacer length; clonal growth; clonal integration; ramet class